Banco Interamericano de Desenvolvimento e Política Urbana no município de Belém: tensões e compatibilidades no modelo de gestão de cidades e no discurso da participação social - SANTANA, Joana Valente (Universidade Federal do Rio de Janeiro, 2017)
This thesis aims at learning the meaning of the Inter-American Development Bank (IDB) multilateral financial aid for Latin American countries, particularly Brazil, and tries to identify how the bank operates, through several mediations, in the defense of continuing capital accumulation. Our research identified that IDB operates not only as a policy financing agent, but mainly as the general intelligentsia of the interests of the elite by prescribing management models for: a) federal governments through the Country Documents and Strategy Documents (mainly about State reform themes connected to the neoliberal recommendation of structural adjustments to facilitate – among other things – the payment of the foreign debts by the central governments); b) municipal governments, through the dissemination of a city management model, urging local authorities to take over the execution of social policies with efficiency and economy in the public social expenditures, and implement sectoral and focused policies (for the “urban poor”), while preparing, at the same time, the city infrastructure in order to attract corporate investors besides forming “partnerships” with society (enhancing social participation) and private initiatives. On the other hand, this thesis also analyzes the city management model, based on the democratic perspective of the Urban Reform (specially the city democratic management principle), which is contrary to the neoliberal model recommended by IDB, thus favoring working classes factions, validating democratic processes (direct democracy) in the defense of citizenship, referenced by socialist ideologies. Such democratic model started to be widely used in Brazil, particularly when some municipalities started to be run by Workers Party mayors (as of 2000). At that moment, there was some expectation regarding the creation of proposals incorporating the political advances in the social sector as provided in the Federal Constitution of 1988. In the city of Belém, State of Pará, a left winged front run by the Workers Party won the elections in 1996, renewing its mandate until 2004. At the level of government planning, the Municipal Authority of Belém claimed for a political management connected to the city management democratic model, based on the principles of social participation and state democratization. Through a project financed by IDB (Habitar Brazil Program – IDB), the Local Development Plan “Riacho Doce” and “Pantanal”, the city had to comply with a series of demands, such as the signature of an Acceptance Contract by 80% of the users. Since the city authorities favored an alternate planning, which enhanced the participation of the local residents in all stages of the project, the research tried to identify points of conflict and of compatibility between the city management models and the social participation notion (a neoliberal proposal by IDB) of democratic base. The results indicate that the city management democratic model discourse presents some elements of conflict (contrary trends), mainly expressed by the proposals for the universalization of rights, inter-sectoral policies, and allusions to socialist ideals. Elements of compatibility were also found (adaptation of the Plan in order to guarantee the funds), but the overall result appointed to more points of difference than of compatibility between the neoliberal and the democratic agendas.